Clustering of E-mails Using Pattern Matching (International Journal of Engineering and Computer Science, 2015)
Email communication is one of the most effective and popular way of communication today. Sending and receivingof messages for exchange of information is done by people every day. E-mail communication is popularly used way ofcommunication. E-mail data that are now becoming most important way of inter and intra organizational written communicationfor many companies. Clustering is defined as creating group of similar objects. The cluster shows the similar emails exchangedbetween the users and for finding the text similarities to cluster the users, we are using the Pattern i.e., by considering thedifferent Threshold value the similar words exchanged between the users, Threshold value shows the frequency of the words usedand we have graphically represented the cluster in the form of Bar charts.